Malaysian graduates of Middle-Eastern universities: perspectives on human capital development - Alavi, Khadijah; Md. Sail, Rahim; Abdul Mutalib, Lukman; Ahmad, Anwar; Tarjo, Shamsul Shah; Abdul Razak, Nor Ellina (Universiti Putra Malaysia Press, 2013)
Malaysian youth who graduate from Middle-Eastern Universities are important and suitable human capital for Malaysia as they are equally knowledgeable and skilful as any local or western university graduates. In fact, the additional components in their study programmes such as Islamic philosophy, principles and ethics based on the al-Quran and Hadith form the foundation for integrity and accountability. Science, technology and Islamic knowledge are critical ingredients of human capital development in any organisation to ensure high productivity embedded with integrity, professionalism and accountability. The main purpose of this study was to determine the factors affecting human capital development among Malaysian graduates of Middle-Eastern universities. The factors identified were their preparation before leaving for their studies, their studying practices, their academic achievements, their personality development and their experiences (good and bad) while they were in Middle-Eastern universities. This study used the quantitative design on 386 Malaysian graduates who graduated from Middle-Eastern universities; these graduates were serving in several government and private-sector agencies. The findings indicated that all the independent variables had significant positive relationship with the dependent variable, that is, the process of human capital development with r values ranging from .280 (preparation before going to Middle- Eastern universities) to .546 (personality development). The findings of this study suggest that Malaysian graduates of Middle- Eastern universities are an important source of human capital that can steer the future development of the nation alongside their peers who graduate from local and western universities.